1986
DOI: 10.1021/np50048a043
|View full text |Cite
|
Sign up to set email alerts
|

Minor Steroidal Sapogenins from Fenugreek Seeds, Trigonella foenum-graecum

Abstract: In our continuing chemical analysis (1-3) of Trigonella foenum-graecum L. (Leguminosae), we report here nine steroidal sapogenins found in the seeds. In addition to six previously reported compounds (4-7), three more minor sapogenins, smilagenin, sarsa-sapogenin, and yuccagenin, were identified. EXPERIMENTAL Extraction and isolationof sapogenins.-Air-dried, powdered seeds (500 g) of T. foenumgraecum (Fenugreek, Ethiopian variety) cultivated at our institute farm were defatted with «-hexane. The marc was extrac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 1 publication
0
20
0
Order By: Relevance
“…Additionally, dietary fiber may significantly contribute to fenugreek's activity in lowering blood glucose and cholesterol (Gupta, Jain, & Thakur, 1986; Valette, Sauvaire, Baccou, & Ribes, 1984). Another main component of fenugreek which has been reported to have modulating effect on dyslipidemia is saponin (Fuller & Stephens, 2015; Uemura et al, 2011; Verma et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, dietary fiber may significantly contribute to fenugreek's activity in lowering blood glucose and cholesterol (Gupta, Jain, & Thakur, 1986; Valette, Sauvaire, Baccou, & Ribes, 1984). Another main component of fenugreek which has been reported to have modulating effect on dyslipidemia is saponin (Fuller & Stephens, 2015; Uemura et al, 2011; Verma et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Another main component of fenugreek which has been reported to have modulating effect on dyslipidemia is saponin (Fuller & Stephens, 2015; Uemura et al, 2011; Verma et al, 2016). Indeed many studies showed that the hypocholesterolemic effect of fenugreek was due to the saponin‐rich subfraction (Gupta et al, 1986; Sauvaire, Ribes, Baccou, & Loubatieères‐Mariani, 1991). A study by Chen et al showed that saponins can effectively accelerate cholesterol metabolism and process of reverse cholesterol transport (RCT), meanwhile prohibit cholesterol synthesis and therefore effectively reduce TC level (Chen et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Dietary fibers and saponins that are present are specifically known to enhance hypoglycemic activity. Additionally, dietary fiber may significantly contribute to fenugreek's activity in lowering blood glucose and cholesterol ( 36 ).…”
Section: Discussionmentioning
confidence: 99%
“…3b) (Gupta et al 1986) that is Skaltsa 2002). Isoleucine, being an underlying branchedchain amino acid (BCAA), found to be the key precursor for synthesis of 4-hydroxyisoleucine and serves as an efficient factor in regulating the insulin secretion in animals (Broca et al 2000) and making it potentially useful in the control of diabetes (Acharya et al 2008).…”
Section: Seed Chemical Compoundsmentioning
confidence: 95%